Presence and Absence in Margaret Atwood’s Dearly - Pilar Sánchez-Calle (Canada and Beyond)
In Morning in the Burned House (1995), Margaret Atwood includes a sequence of elegiac poems mourning the process of her father’s illness and death. Her subsequent collection, The Door (2007), while not explicitly elegiac, explores topics such as memory, aging, death, loss, and decay. These subjects are often central to both traditional and contemporary elegies. Other poems in this volume deal with writing and poetry, examining their capacity to offer consolation in the face of death, a key aspect of elegy. Drawing on critical studies of elegy in contemporary English-language poetry and on the role of elegy in Atwood’s poetry, this essay analyses the elegiac dimension of Dearly (2020), Atwood’s most recent poetry collection. Many of these poems are dedicated to her partner Graeme Gibson, who was diagnosed with vascular dementia in 2017 and passed away in 2019. Through close readings and formal analysis, I aim to demonstrate how these elegiac poems articulate a psychic landscape of mourning where separation after death is rejected and an alternative space for reunion with the deceased is created. Atwood moves beyond simple lamentation, exploring the liminal space between life and death, presence and absence.